Andean Wetlands: Governance and Community Agency in the Bolivian Altiplano - Perales Miranda, Víctor Hugo (2026)
This paper examines the critical situation of the Andean wetlands in the Bolivian Altiplano, socio-ecological ecosystems vital to the Aymara indigenous communities. These wetlands regulate the water cycle, store water, and provide forage for camelid livestock, fundamental to the local economy. However, they face dual threats: climate change, characterized by glacier retreat and altered rainfall patterns, and the pressure from large hydraulic projects that divert water to cities, causing a metabolic fragmentation that affects the ecosystem and rural communities. The conflict at the Taypichaca dam reflects a clash of paradigms between traditional community governance, based on ancestral systems and self-management, and a centralized technocratic model that prioritizes urban supply. The research reveals that communities, far from being passive, implement strategies such as "the locks" to negotiate and resist state intervention, demonstrating epistemic agency and adaptation. It is concluded that the solution lies in adopting polycentric governance that integrates and values local knowledge, promotes socio-environmental justice, and allows real participation of communities in water management, ensuring sustainable and equitable development in the Bolivian Altiplano.